Is Early Treatment with a Cervical Pessary an Option in Patients with a History of Surgical Conisation and a Short Cervix? - Kyvernitakis, I.; Khatib, R.; Stricker, N.; Arabin, B. (Geburtshilfe und Frauenheilkunde, 2014)
Objective: Patients with a history of one or more conizations have an increased risk of spontaneous preterm birth (SPTB). The aim of this study was to investigate the outcome of pregnancies in patients with a history of conization and early treatment with a cervical pessary. Methods: In this pilot observational study we included 21 patients and evaluated the obstetric history, the interval between pessary placement and delivery, gestational age at delivery, the neonatal outcome and the number of days of maternal and neonatal admission. Results: Among the study group of 21 patients, 20 patients had a singleton and one had a dichorionic/diamniotic twin pregnancy. At insertion, the mean gestational age was 17 + 2 (10 + 5–24 + 0) weeks and the mean cervical length was 19 (4–36) mm. Six patients presented with funneling at insertion with a mean funneling width of 19.7 (10–38) mm and funneling length of 19.9 (10–37) mm. Five patients had already lost at least one child due to early spontaneous preterm birth and another five had at least one previous abortion, who have now delivered beyond 34 weeks. The mean gestational age at delivery was 38 (31 + 1–41 + 0) gestational weeks and the mean interval between insertion and delivery was 145 (87–182) days. Conclusion: Our findings suggest a beneficial effect of an early pessary placement for patients at high-risk for preterm birth due to conization.
Keywords: conisation; pessary; cerclage; cervical shortening; preterm birth